Direct supervision of physiotherapists improves compliance with clinical practice guidelines for patients with hip fracture: a controlled before-and-after study. Issue 26 (17th December 2020) - Snowdon, David A.; Leggat, Sandra G.; Harding, Katherine E.; Scroggie, Grant; Hau, Raphael; Darzins, Peteris; Taylor, Nicholas F
Abstract: Purpose: To determine if the addition of direct supervision to usual clinical supervision practice of physiotherapists can improve compliance with clinical practice guidelines and post-surgical outcomes for inpatients with hip fracture. Methods: A controlled before-and-after study was conducted on two acute orthopedic wards. Junior and mid-level physiotherapists on one ward were provided with direct supervision during their post-operative management of patients with hip fracture. Physiotherapists on the comparison ward received usual reflective supervision. The primary outcome was patient compliance with the hip fracture guideline to mobilize on the day following surgery. Secondary patient outcomes included physical function on the fifth post-operative day. Results: Data were collected from 290 patients with acute hip fracture. Patients at the direct supervision site were more likely to mobilize on the day after surgery [OR 3.14, 95% confidence interval (CI) 1.41–7.01; p = 0.005] and by the second post-operative day (OR 4.62, 95% CI 2.31–9.23; p < 0.001) compared to patients at the comparison site. Patients walked further on the fifth post-operative day ( p < 0.001) with less assistance from therapists ( p = 0.044). Conclusions: The addition of direct supervision improved physiotherapists' compliance with hip fracture guidelines and walking endurance and independence in hospitalized patients with hip fracture. Implications for rehabilitation: The addition of a direct supervision model, where physiotherapists are directly observed in their management of patients with hip fracture, to usual practice supervision improved early mobilization of patients with hip fracture Direct supervision appears to be an effective guideline implementation strategy that can improve care and outcomes for hospitalized patients with hip fracture